Two ways power flow with renewable energy integration - Sarnon, Mohd Zaki (2013)
Today’s electric grid was designed to operate as a vertical structure consisting of generation, transmission and distribution and advanced control support devices for reliability, stability and efficiency. However, our conventional system grid now facing new challenges including the penetration of Renewable Energy Resources (RER). The advanced development of power grid system for future will give immediate impacts of anew connection such as power flow direction, protection, voltage profile, power quality and stability. This project aims to find out the performance of smart grid system with renewable energy integration and focuses on power flow studies. Thus, modeling of electrical power grid for smart grid is a part of the project throughout some of conventional calculation. The calculation of power flow is based on Newton Raphson method and was developed with existing software for analysis. The power flow calculation aim to evaluate the parameters of that particular performance such as voltages, currents, real and reactive power flow in a system under a given load conditions. The standard test system that used was IEEE 14-Bus System and modification was made to the grid within the integration of renewable energy. Effect of FACTS also implemented in this project as additional case to study the power flow. The comparisons and results from simulation show the variation of power flow when the renewable energy and FACTS devices were applied. In conclusion, this project focus on research to study the power flow in the smart grid with renewable energy integration modeled.